1990
DOI: 10.1093/oxfordjournals.humrep.a137038
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies in unselected patients with repeated abortion

Abstract: We have studied, prospectively, the incidence of several antiphospholipid antibodies (lupus anticoagulant, anticardiolipin, anti-phosphatidylserine, anti-phosphatidic acid, anti-phosphatidylinositol and anti-thromboplastin antibodies) in 65 consecutive patients with two or more (range 2-8, mean 3.1) abortions. Lupus anticoagulant activity was detected in seven (10.7%) patients and all of them exhibited other antiphospholipid antibodies. Of the previous pregnancies in these seven women, 88% had ended in spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Abnormal autoimmune function has been suggested to impede female fertility (9,10) and to increase the risk of pregnancy loss (6,(17)(18)(19)(20), a risk we strive to reduce via timely diagnosis and treatment (9). Women were, therefore, designated as autoimmune, or not, before data analysis for this study was initiated.…”
Section: Methodsmentioning
confidence: 99%
“…Abnormal autoimmune function has been suggested to impede female fertility (9,10) and to increase the risk of pregnancy loss (6,(17)(18)(19)(20), a risk we strive to reduce via timely diagnosis and treatment (9). Women were, therefore, designated as autoimmune, or not, before data analysis for this study was initiated.…”
Section: Methodsmentioning
confidence: 99%
“…Among others, we then expanded this finding by demonstrating that lupus anticoagulant was only one sign of a polyclonal activation of autoimmune function [83]. A large number of studies followed, initially primarily concentrating on the association between lupus anticoagulant and a positively charged APA, the so-called anticardiolipin antibody (ACA) [65,[84][85][86]. We, and other investigators, then demonstrated that lupus anticoagulant was closely associated not only with ACA but with a broad array of abnormally elevated APAs and that APA abnormalities did not appear in isolation, but were part of a polyclonal B-cell activation and could also appear in association with organ-specific autoantibody findings [66,[87][88][89][90].…”
Section: Autoimmune-associated Reproductive Failurementioning
confidence: 99%
“…In the study by Rai et al [71] aspirin treatment was started after diagnosis of pregnancy. In both studies [71,72], the outcomes in the aspirin-only group were worse than those in other series with the same schedule [56,[58][59][60][61]74].…”
Section: Management Of Obstetric Antiphospholipid Syndromementioning
confidence: 99%